Pentingnya Pola Hidup Sehat Di Era New Normal - Silvia Basri, Merri; Nahdah Syariqoh, Fitria; Lamsihar Pakpahan, Dian (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
The Covid-19 pandemic has changed many things in an instant. Therefore, a change in cleanand healthy living behavior is needed in the new normal era. In implementing the New Normalphase, where the new normal is not a condition where there is no more Covid-19 virus,socialization is needed in the community to break the chain of spreading the Covid-19 virus.The service is carried out to the community in Laksamana Village, Dumai City District, RiauProvince. The method used is outreach to the community. The purpose of serving the KKNBalek Kampung Kelurahan Laksamana 2022 service to the community as a form of knowledgetransfer about ways to implement behavior change as a preventive effort for Covid-19. Theresults obtained in this service are that the community has the knowledge and ability to apply,motivate, and adapt to family members, and the community is a pioneer in making changes toclean and healthy living behavior in the new normal era.